The omega-3 index in patients with heart failure: A prospective cohort study. (January 2019) - Berliner, Dominik; Mattern, Sarah; Wellige, Mareike; Malsch, Carolin; Güder, Gülmisal; Brenner, Susanne; Morbach, Caroline; Deubner, Nikolas; Breunig, Margret; Kiefl, Rosemarie; Angermann, Christiane E.; Ertl, Georg; et al.
Highlights: In patients hospitalized for decompensated heart failure, marked depletion of omega-3 fatty acids was detected. Although the Omega-3 index was associated with established risk markers in heart failure, it did not predict mortality risk. The lack of predictive power of the omega-3 index might be due to a very homogeneous distribution in this cohort. Abstract: Background: Epidemiologic studies on the omega-3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in heart failure are scarce, while one large intervention trial demonstrated a modest benefit. Methods: This is a secondary analysis from the Interdisciplinary Network Heart Failure (INH) program. Patients hospitalized for systolic heart failure were enrolled and followed for 36 months. At baseline, whole blood samples from 899 patients were analyzed for fatty acid composition using a standardized analytical procedure (HS-Omega-3 Index®, O3-I). Associations of the O3-I with markers of heart failure severity, clinical characteristics, biomarkers, and mortality were analyzed. Results: The mean O3-I was 3.7 ± 1.0%. Patient mean age was 68 ± 12 years (72% male, 43% in New York Heart Association (NYHA) class III or IV, mean LVEF 30 ± 8%). During follow-up 258 patients (28.7%) died. After adjustment for potential confounders, the O3-I showed weak associations with uncured malignancy, end-systolic diameter of the left atrium, left ventricular end-diastolic and end-systolic diameters, and blood lipids and other laboratory parameters (all p  < 0.05), but not with NYHA class, left ventricular ejection fraction, and the underlying cause of heart failure. The O3-I did not predict the 3-year mortality risk. Conclusions: Our results show a marked depletion of omega-3 fatty acids in patients hospitalized for decompensated heart failure (suggested target range 8–11%). Although the O3-I was associated with a panel of established risk indicators in heart failure, it did not predict mortality risk. Clinical Trial Registration: www.controlled-trials.com ; ISRCTN23325295